2008
DOI: 10.1021/jf073272v
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Antioxidant and Biological Activities of Carvacrol, Thymol, and Eugenol Derivatives

Abstract: Four derivatives of thymol, carvacrol, and eugenol were synthesized: 4-(hydroxymethyl)-5-isopropyl-2-methylphenol, 4,4'-methylenebis(5-isopropyl-2-methyl)phenol, 4-allyl-6-(hydroxymethyl)-2-methoxyphenol, and 4-(hydroxymethyl)-2-isopropyl-5-methylphenol. The obtained derivatives showed remarkably better antioxidative properties according to 1,1-diphenyl-2-picrylhydrazyl assay (50% inhibitory concentrations = 4-156 microg/mL) and Rancimat assay (protection factors = 1.55-5.84) when compared with parent compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
2
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(151 citation statements)
references
References 34 publications
8
127
2
6
Order By: Relevance
“…A diet supplemented with 100 mg/kg carvacrol-thymol (1 : 1) blend reduced weaning-induced oxidative stress. Both carvacrol and thymol have free radical scavenging activity (Mastelic et al, 2008;Archana et al, 2009;Safaei-Ghomi et al, 2009). In the current study, increased activity of antioxidants in the jejunum was observed in the weaned-CB group compared with the weaned group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diet supplemented with 100 mg/kg carvacrol-thymol (1 : 1) blend reduced weaning-induced oxidative stress. Both carvacrol and thymol have free radical scavenging activity (Mastelic et al, 2008;Archana et al, 2009;Safaei-Ghomi et al, 2009). In the current study, increased activity of antioxidants in the jejunum was observed in the weaned-CB group compared with the weaned group.…”
Section: Discussionmentioning
confidence: 99%
“…Both carvacrol and thymol possess in vitro ROSscavenging activity (Mastelic et al, 2008). In addition, it has been demonstrated that either carvacrol or thymol alone, or in combination, has antibacterial properties to inhibit growth of E. faecalis and E. coli (Michiels et al, 2009;Guarda et al, 2011;Gutiérrez-Fernández et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 H and 13 C-NMR spectra were obtained on JEOL JN ECA -500 (500 MHz). Mass spectra were recorded on Shimadzu GCS QP-2010S.…”
Section: Instrumentationmentioning
confidence: 99%
“…Oxidative stress, caused by an imbalance between antioxidant systems and the production of oxidants, seems to be associated with many diseases, especially cancers, cardiovascular diseases and inflammatory disorders [1]. The mechanisms by which these pathologies grow generally involve oxidative alteration of physiologically critical molecules, including proteins, lipids, carbohydrates, and nucleic acids, along with the modulation of gene expression and inflammatory response [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation